Analisis Kesalah pahaman Kisah Israiliyat dalam Penafsiran Al-Qur’an - Aprilita Hajar; Abdul Kadir Riyadi (Studia Quranika, 2023)
Deviation in Qur'anic interpretation is exceedingly perilous, and one of the things that harms Muslims' faith is the advent of Ad-Dakhil in Qur'anic interpretation. Israiliyah's narrations, particularly those that focus on historical accounts, are a frequent source of Ad-Dakhil's influence. The underlying truths about the people's history in the past are rediscovered in this inquiry using a qualitative methodology or library research. Muslims may also be misled about their faith due to misconceptions about the Israiliyat account in the Qur'an. As a result, they tend to accept and believe in teachings or stories that contain Khuraad and deviations.